Pengaruh Capital Adequacy Ratio, Inflasi, Financing Deposit Ratio dan Biaya Operasional Per Pendapatan Operasional Terhadap Non Performing Financing Bank Umum Syariah di Indonesia - Muhammad Farhan Arsyad; Nur Diana; Junaidi Junaidi (Universitas Islam Malang, 2023)
This study aims to examine the impact of Capital Adequacy Ratio (CAR), Inflation, Financing Deposit Ratio (FDR) and Operational Cost per Operating Income (BOPO) on Non Performing Financing (NPF) in order to assess the financial performance of Islamic commercial banks illustrate in Indonesia to minimize the occurrence of funding issues occurring in the period 2018-2021. The data used in this study comes from the quarterly published financial reports of Islamic commercial banks consisting of Bank Muamalat, Bank Victoria Indonesia and Bank Rakyat Indonesia Syariah, Bank Negara Indonesia, Bank Mega Syariah, Bank Jabar Banten Syariah, Bank Panin Dubai Syariah, Bank Central Asia Syariah, Bank BTPN Syariah, Bank Syariah Indonesia for the period 2018 to 2021, published by Bank Indonesia. The data collected were analyzed using multiple linear regression analysis. The independent variables used in this study are capital adequacy ratio, inflation, funding deposit ratio, and operating costs per operating income. While non-performing financing is the dependent variable.Keywords: Non-Performing Financing (NPF), Capital Adequacy Ratio (CAR), Inflation, Financing Deposit Ratio (FDR) and Operational Cost per Operating Income (BOPO)